2022
DOI: 10.1038/s41467-022-28691-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of estrogen receptor alpha by YAP reveals the Hippo pathway as therapeutic target for ER+ breast cancer

Abstract: Extensive knowledge has been gained on the transcription network controlled by ERα, however, the mechanism underlying ESR1 (encoding ERα) expression is less understood. We recently discovered that the Hippo pathway is required for the proper expression of ESR1. YAP/TAZ are transcription coactivators that are phosphorylated and inhibited by the Hippo pathway kinase LATS. Here we delineated the molecular mechanisms underlying ESR1 transcription repression by the Hippo pathway. Mechanistically, YAP binds to TEAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…Previously, VGLL3 has been shown to enhance breast cancer cell proliferation and drive systemic autoimmunity 62 , 63 . Recently, VGLL3 has been shown to bind to TEAD and suppress ESR1 gene expression 64 . Here we show that VGLL3 functions as a transcription co-activator to induce the expression of YAP-suppressed genes, suggesting complexed and context dependent functions of VGLL family of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, VGLL3 has been shown to enhance breast cancer cell proliferation and drive systemic autoimmunity 62 , 63 . Recently, VGLL3 has been shown to bind to TEAD and suppress ESR1 gene expression 64 . Here we show that VGLL3 functions as a transcription co-activator to induce the expression of YAP-suppressed genes, suggesting complexed and context dependent functions of VGLL family of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In the METABRIC cohort, tumors with early mortality (within 5 years of sample collection) showed consistent enrichment of pathways that are known to contribute to epithelial to mesenchymal transition, angiogenesis, and stemness. Enriched pathways, including TGF‐beta (Band & Laiho, 2011 ) and YAP (Ma et al , 2022 ), have been suggested to directly crosstalk and repress the estrogen receptor signaling pathway. Concurrently, MEK (Fujii et al , 2011 ) and PI3K/AKT/MTOR (Ciruelos Gil, 2014 ) have been implicated as key primary resistance mechanisms in endocrine‐resistant ER + breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, nearly 79% cases are estrogen receptor α (ERα)-positive, which is a hormone receptor that mediates estrogen effect and regulates transcription and expression of estrogen-sensitive genes. Aberrant ERα activity has been observed in a variety of diseases, including breast cancer. Meanwhile, several pieces of accumulated evidence have suggested that ERα plays an important role in the development and progression of breast cancer .…”
Section: Introductionmentioning
confidence: 99%